(untitled) - Bennett-Alexander, Dawn D. (Boston, MA., 2004)
Bennett-Alexander and Hartman;s, Employment Law for Business, 4/e, addresses law and employment decisions from a managerial perspective. It is intended to instruct students on how to manage effectively and efficiently with full comprehension of the legal ramifications of their decisions. Students are shown how to think and analyze employment law facts using concrete examples of management-related legal dilemmas without clear-cut solutions. The methods of arriving at resolutions are emphasized, so that when the facts of the workplace problem are not quite the same, the student can still reach a good decision based on the legal considerations required by law, which remain relevant.
Keywords: Labor laws and legislation,Discrimination in employment; Law and legislation; United states,United states